CHALLENGES IN PUNCTUATION USAGE AMONG LIBYAN EFL SECONDARY STUDENTS - Alruwani, Murad Mohammed; Senowarsito; Andris Susanto, Dias (English Review: Journal of English Education, 2025)
Abstract: This study investigates the challenges in punctuation usage among Libyan EFL secondary students, with the primary objective of identifying specific types and underlying causes of punctuation errors in their writing. A qualitative descriptive methodology was employed, involving a sample of 20 first-year secondary students at Zlitin Central School who participated in narrative writing tests. These tests were specifically designed to identify and categorize punctuation errors. Additionally, semi-structured interviews were conducted with four experienced English language teachers from the same school to gain deeper insights into instructional practices and their perceptions regarding students' punctuation difficulties. Data analysis included thematic analysis techniques, resulting in the identification of three main categories of punctuation errors: omission, misinformation, and addition. Among these categories, omission errors, particularly the omission of commas, were most prevalent, reflecting significant gaps in students' punctuation understanding and application. Interviews revealed critical contributing factors, including linguistic interference from the students' first language (Arabic), insufficient explicit instruction regarding punctuation rules, limited practical writing exercises, and a general lack of awareness of punctuation's role in effective written communication. This study highlights the necessity of targeted instructional strategies and curriculum improvements aimed at addressing these challenges. Recommendations include integrating explicit punctuation instruction into the Libyan EFL curriculum, employing error analysis techniques in classroom activities, and enhancing practical writing exercises and feedback mechanisms. By focusing on these pedagogical interventions, educators can significantly improve students' punctuation proficiency, thereby enhancing their overall writing skills and academic performance.